HOW MALAYSIAN DIPLOMA STUDENTS COMPENSATE FOR LANGUAGE LEARNING: A SURVEY STUDY - Nur Ain Binti Abdul Malek; Siti Ainul Ayzan Binti Ayub; Tg Nur Liyana Binti Tengku Mohamed Fauzi (Journal of Islamic, Social, Economics and Development, 2023)
This study was conducted to investigate the compensatory strategies used by Malaysian students in a public university in learning English. The research gap that this study aims to fill is the lack of research on the use of compensatory strategies by Malaysian students. To achieve the main objective, the study conducted a survey using questionnaire items from Oxford's (1990) LLS focusing only on compensatory strategies and distributed to first and third semester students. Based on the responses of 152 respondents, the study found that students prefer to use word substitutions and gestures when they cannot think of an English word. They also tend to make guesses when trying to understand unfamiliar English words and predict what the other person will say next. In contrast, students rarely think of new words, and they are unable to read English without looking up each new word. The use of means and standard deviations provided a more accurate measure of the data obtained from the survey. The results suggest that the use of compensatory strategies is widespread among Malaysian students and that they prefer certain strategies over others. The study highlights the importance of considering compensatory strategies in language learning and teaching, especially for learners who are new to the language. The study concludes that a better understanding of compensatory strategies can help teachers develop appropriate instructional materials and strategies that address learners' specific needs.